Brazil : media from the country of the future - Robinson, Laura (Sociologist); Schulz, Jeremy; Williams, Apryl; Aguiar, Pedro Beja (Emerald Publishing Limited, 2017)
This book explores five key themes: the new face of news and journalism, social movements and protest, television, cinema, publicity and marketing, and media theory. Chapters reflect the Brazilian case as a laboratory for exploring the evolving media environment of one of the world's most fascinating societies.
Keywords: Mass media -- Brazil.; Journalism -- Brazil.; Communication -- Social aspects -- Brazil.; Brazil.; Brasilien; elektronické knihy; electronic books